2020
DOI: 10.15520/ijcrr.v11i01.785
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Career Development and Servant Leadership on Employee Performance with Work Motivation as an Intervening Variable in the Employment Agency and Human Resources Development Denpasar City

Abstract: The purpose of this study was to determine and test the effect of career development, servant leadership and work motivation on employee performance, to determine and test the effect of career development and servant leadership on employee work motivation at the Human Resources and Human Resources Development Agency in Denpasar City and to know and test the effect career development and servant leadership on employee performance through work motivation as an intervening variable. The population of this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…(2020), human resources development is the integrated use of systems, practices and policies to develop and retain personnel for the firm to achieve its desired goals and sustainability. However, Agung and Widnyana (2020) pointed out that human resources development needs a continuous assessment to discover any problems that might arise during the human resources development process. The study also found that compensating human resources positively affects the economic sustainability of Jordanian banks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020), human resources development is the integrated use of systems, practices and policies to develop and retain personnel for the firm to achieve its desired goals and sustainability. However, Agung and Widnyana (2020) pointed out that human resources development needs a continuous assessment to discover any problems that might arise during the human resources development process. The study also found that compensating human resources positively affects the economic sustainability of Jordanian banks.…”
Section: Discussionmentioning
confidence: 99%
“…Human resources development is the integrated use of practices, systems and policies to develop and maintain a company's workforce to achieve its desired goals and sustainability (Mijatovi c et al, 2020). However, a continuous assessment of human resources is necessary for the growth of human resources (Agung and Widnyana, 2020). The human resources in Jordanian banks may encounter a variety of issues, such as a lack of skills and knowledge (Eglash et al, 2020).…”
Section: 23mentioning
confidence: 99%
“…In another study, SL was positively related to organizational commitment, job satisfaction, and intrinsic work satisfaction (Avolio et al, 2009). Additionally, Faizah et al (2020) found that SL positively affected employee motivation and workplace performance. Joseph and Winston (2005) found that employee perceptions of trust (from the servant leader) were positively related to their trust in both the servant leader and the organization.…”
Section: Emergence Of Transactional and Transformational Leadership R...mentioning
confidence: 97%